Prawo karne w konstytucjach sejmu koronacyjnego z roku 1588 - Wiązek, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The author attempts to select and then to analyse criminal law provisions of the constitutions of the Coronation Sejm of 1588. Using a dogmatic-linguistic interpretation, applied together with the historical-descriptive method, he seeks to present the results of his explorations in a broad historical perspective. His intention is to illustrate the evolution of some institutions of Polish criminal law in the past. Drawing on comparative legal research, he presents the results of his studies in a broad historical-legal perspective. The author ends with confronting his final conclusions with theses formulated by some other, outstanding scholars, hoping that his research will inspire other explorers of the subject matter.
Keywords: historia prawa; prawo karne; ewolucja sądownictwa; odpowiedzialność karna; ustawodawstwo polskiego parlamentu w przeszłości